Tom and Jerry in US-China Relations - huswatun miswar, syarifah; Miswar, Syarifah Huswatun (Westscience Press, 2024)
In the liberal concept, especially neoliberal, countries that cooperate tend to have less potential for conflict. However, this does not apply to US-China relations which are more often in tension, but until the Biden administration China-America still has a strong dependence in economic relations. The China-US relationship is often referred to as the